iRel: software for implementing pairwise relatedness estimators and evaluating their performance - Gonçalves da Silva, Anders; Russello, Michael A. (Conservation genetics resources, 2011)
The online program iR el calculates the individual multilocus pairwise relatedness indices of Queller and Goodnight (Evolution 43: 258–275 1989 and Lynch and Ritland (Genetics 152:1753–1766, 1999 ), and evaluates their statistical properties given an empirical allele frequency distribution. In particular, it estimates misclassification rates between different relatedness categories and the proportion of variance explained by true relatedness for each of the indices based on the empirical allele frequency distribution and Monte Carlo simulated dyads of different relatedness categories. This approach allows the user to evaluate which index is better suited for a particular dataset, enhancing inferences associated with a wide range of research questions in ecology, animal behavior and conservation.